Telaah Filosofi Surah Al-Fatihah dalam Perspektif Psikologi dan Manajemen Pendidikan era Revolusi Industri 4.0 - Al-Mahali, Ahmad Mustofa Jalalluddin (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2019)
At present, very little of what children in schools do is really taken into account their technological abilities which in fact are digital natives that cannot be taught in conventional ways. Conventional education institutions, especially Islamic based institutions, are many who experience confusion in this matter. in this perspective Penilis tried to take part in dealing with this problem by raising the first surah from the Qur'an. Al-Fatihah as Al-Shifa (The Cure) gives protection to Satan and his followers and strengthens the human heart towards the first. Al-Kanz (Treasure) indicates that the surah is a storehouse of endless knowledge which is an abstract document of the Koran. It is not difficult to understand when Qutb carefully notes that the Qur'an presents Islam as "a serious, dynamic and pragmatic doctrine", and as an ethical system is a reflection of this doctrine whose substance is all religions depend on the Unity of God concept with which God presents an irreducible core of how He wants all beings to know Him, relate to Him, and live in His world. This paper aims to examine the philosophy of Surah Al-Fatihah in the perspective of psychology and education management in the industrial revolution era 4.0. The conclusions of this work are: 1) The concept of al-Islam for the sake of li kuli era wa al-makan (Islam is a religion that is suitable for all era and area contexts) needs to be proven by Muslims themselves with the life guidelines that they hold, namely Al Qur'an and Hadith; 2) al-Fatihah position on the Qur'an such as abstracts in scientific research or resumes in reports, because it is a miniature essence and concept map of the Qur'an itself, from the beginning the reader becomes familiar in the outline of the subject he should find in Al-Qur'an; 3) al-Fatihah is a resume of guidance for Muslims (Qur'an) to carry out their duties as servants and caliphs on earth. Therefore, it must adhere to the principles and values ??contained in the standard operating procedures for progress management in the Industrial Revolution era 4.0; 3) Apart from the formal decline in the influence of religious ideas in the public discourse of the Industrial Revolution era 4.0, secular power structures have usurped the transcendent dimension of religion in which Islamic societies build their legitimacy and representation principles, in this situation Al Fatihah (a systematic code) who is able to distinguish which element of fact is supported or rejected by Islam through al-Fatihah as its filter.